Professional and social competences in agrarian specialists: Theoretical aspects - RIDEI, Nataliia; GUSAK, Kateryna (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
We assessed the current knowledge towards forming professional and socialcompetences in agrarian specialists. We analyzed the process of preparing agrarianspecialists in higher education of Ukraine. We reviewed definitions of „professionalcompetence of agrarian specialist” and „social competence of agrarianspecialist”.